The Influence of Thai Traditional Philosophical Thought on Contemporary Educational Policies - Somchai Rakpathum; Ananya Silpachai (PT. Berkah Smart Academica, 2025)
This study explores the foundational role of Thai traditional philosophical thought in shaping the landscape of contemporary educational policies in Thailand. Historically rooted in a synthesis of Theravada Buddhism, Brahmanism, and local animistic beliefs, Thai philosophy emphasizes holistic development, moral integrity, and the